Global, regional, and national burden of gout in elderly 1990-2021: an analysis for the global burden of disease study 2021 - Yilan Li; Zhaopeng Chen; Baijie Xu; Gengmao Wu; Qiongyu Yuan; Xiaoqian Xue; Yue Wu; Yudan Huang; Shouqi Mo (BMC, 2024)
Abstract Background Gout, an inflammatory arthritis, disproportionately affects the elderly due to hyperuricemia, leading to significant health-related quality of life impairments and escalating healthcare costs. However, a comprehensive global analysis focusing on the elderly population is needed to inform effective interventions. Methods Utilizing data from the Global Burden of Disease Study 2021, this study assessed the prevalence, incidence, and Years Lived with Disability (YLDs) of gout among individuals aged ≥ 55 years in 204 countries from 1990 to 2021. We also evaluated the impact of high body mass index (BMI) and kidney dysfunction as key risk factors. Results The study identified 37,230,366 cases of gout globally among the elderly, with an age-standardized prevalence rate of 2505.4 per 100,000 population. There was a notable increase in prevalence with an Estimated Annual Percentage Change (EAPC) of 1.08. Similarly, the age-standardized incidence and YLD rates increased, with EAPCs of 0.83 and 1.06, respectively. High-income regions, particularly Australasia and High-income North America, exhibited the highest rates, while Central Latin America and the Caribbean reported the lowest. Males had a higher burden of gout than females. High BMI and kidney dysfunction were significant contributors to YLDs, with their impact more pronounced in regions with higher Socio-Demographic Index (SDI). Conclusion The study found a growing gout burden among the elderly, with substantial regional and gender disparities. It underscores the urgent need for targeted public health interventions, particularly in high SDI regions, to address modifiable risk factors like high BMI and kidney dysfunction and to curb the rising trend of gout prevalence and disability.